Meningkatkan Kesadaran Hukum Pekerja Migran Indonesia: Program Edukasi dan Pendampingan Hukum - Purborini, Vivi Sylvia; Sujiantoro, Hibertus; Refangga, Galih Setyo; Novitasari, Rika (Civiliza Publishing, 2025)
Indonesian migrant workers' legal awareness shows the importance of integrating legal and health literacy to increase their access to basic rights, including health care. The concept of this educational program includes preparing educational materials that are easy to understand, tailored to the literacy level and needs of migrant workers. This educational material not only contains general legal information, but also real case examples to clarify understanding. Legal awareness of Indonesian migrant workers still needs to be significantly improved. Even though there have been efforts to provide educational programs and legal assistance, the level of legal awareness of migrant workers is still relatively low